The Influence of Indigenous Identity and Gender in Perceptions of Behavior in Response to Racialized Police Communication - Sheahan, Chelsea L. (Race and social problems, 2023)
The current studies examined whether the race and gender of a person under suspicion (Studies 1 and 2), as well as the race of the person who called the police (Study 2) influences perceptions of police conduct. Participants read a summary in which the police were called on individuals waiting in a coffee shop (Study 1; N = 133) or sleeping in their dorm common room (Study 2; N = 247). Suspect race (Indigenous vs. White) and gender (male vs. female) were varied in both studies. In Study 2, the race of the person who called the police also varied (Indigenous vs. White). Participants in Study 1 believed race influenced the call to police and the arrest when the suspect was Indigenous (vs. White). Additionally, in both studies, participants were more likely to think that gender influenced the call to police and the arrest when the suspect was described as male (vs. female). The current studies provide new insight regarding public perception of racialized police communication.